(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
We analyze the presence of traditional radio in Spain on the Internet through podcasts. Therefore, we propose three hypotheses: the non-informative genres of traditional radio are those that generate the most audience in podcasts (H1); listeners to digital channels outnumber those who consume radio waves, and humor and sports are genres that produce more interaction. To demonstrate these hypotheses, an analysis of the three generalist radio stations with the largest audience is carried out and we will apply a mixed methodology: interviews with six experts, a survey of 493 people, and analysis of Twitter and Ivoox.